2021
DOI: 10.4028/www.scientific.net/kem.886.97
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Theoretical Concepts of Boron Nitride Nanowires Grown on Nitrides Stainless Steel Surface by Hybrid Gas Phase Process

Abstract: Synthesize of Boron Nitride nanowires were made by utilizing Austenitic hardened steel AISI 316 with a nitriding layer of 15–16 μm thickness. Deposition experiments at deferent substrate temperatures for BN Nanowires productions were carried out with the help of a blended gas stage depositing handle procedure (PVD and CVD). Chemical composition and crystallinity along with the average grain size for BN phases was investigated by using XRD test and FTIR spectrum. The SEM images was used to examine the surface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…As a result, the IR radiation is prevented from passing through the coating and reaching the underlying materials or environment. Figures 1d and 2d demonstrate the calculated energy gap, which demonstrated that the prepared films have a large gap value, and when CdS or ZnS materials were added, the value of that gap decreased, and this is since the generation of secondary levels of compounds added within the energy gap, which narrowed the gap and thus increased optical conductivity which is inversely proportional to the value of the energy gap, these are consistent with the results of researchers [10,18,26].…”
Section: Optical Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As a result, the IR radiation is prevented from passing through the coating and reaching the underlying materials or environment. Figures 1d and 2d demonstrate the calculated energy gap, which demonstrated that the prepared films have a large gap value, and when CdS or ZnS materials were added, the value of that gap decreased, and this is since the generation of secondary levels of compounds added within the energy gap, which narrowed the gap and thus increased optical conductivity which is inversely proportional to the value of the energy gap, these are consistent with the results of researchers [10,18,26].…”
Section: Optical Resultssupporting
confidence: 82%
“…Polyvinyl alcohol is noted for its film-forming prowess, biocompatibility, and processing versatility, which have been exploited in coatings, adhesives, and packaging [5]. Meanwhile, CdS and ZnS-semiconductors with wide bandgaps-are distinguished by optical properties that align well with IR-blocking applications; they exhibit high transparency in the visible spectrum, along with potent IR absorption and reflection [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, control of the structure formation during film fabrication appears to be of great importance for a particular application. Titanium has been utilized in the micro-electro-mechanical system, optoelectronic devices, bio-applications, and mechanical equipment [1][2][3][4][5][6][7][8][9]. Many efforts have been made to obtain (002) orientation.…”
Section: Introductionmentioning
confidence: 99%
“…[6] That human exposure to radiation and its results is one of the important matters that must be studied and paid attention to, especially after the tremendous expansion in the use of nuclear techniques in the field of medicine, agriculture and industry. [8][9][10] There are multiple materials that are used as shields to protect against radiation. The high level of material, in order to diagnose, monitor and treat many medical conditions appropriately, and X-rays have several types according to their energy used for different purposes, there is one type that is used to detect breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The high level of material, in order to diagnose, monitor and treat many medical conditions appropriately, and X-rays have several types according to their energy used for different purposes, there is one type that is used to detect breast cancer. [8] There are X-ray images of the digestive system, and those used to detect bone fractures or blood vessel blockages, and X-rays have some risks to the human body, but the benefits outweigh them for most people. X-rays during pregnancy Most of the imaging procedures are X-ray.…”
Section: Introductionmentioning
confidence: 99%